Effects of the main extraction parameters on chemical and microbial characteristics of compost tea. (June 2016) - Islam, M.K.; Yaseen, T.; Traversa, A.; Ben Kheder, M.; Brunetti, G.; Cocozza, C.
Highlights: Compost tea can feed and protect the crops. Short extraction time maximizes the quality of the compost tea. The compost tea should be applied fresh to preserve its microbial community. Abstract: The rising popularity of compost tea as fertilizer or foliar spray against pathogens has encouraged many researchers to evaluate its performance without standardizing its quality, so obtaining inconsistent and controversial results. The fertilizing and pesticide-like effects of compost tea are due to its chemical and microbiological properties. Therefore, this study aimed to identify the best combination of the compost tea extraction parameters for exalting both chemical and microbiological features. A factorial design was adopted to evaluate the effects of compost/water ratio, extraction time, storage duration and storage temperature in different combination on physical, chemical and microbiological characteristics of compost tea, and the results were elaborated through different statistical analyses. Compost tea nutrients and microorganisms were influenced by compost/water ratio and extraction time. In addition, the storage duration affected the microbial populations, whereas the storage temperature influenced only the fungal population of compost tea. Results suggested that the best combination of the studied parameters was: 1:2.5 compost/water ratio, 2 days of extraction time and the compost tea should be utilized immediately after the extraction, since the storage reduced the microbial populations.